PENGARUH PENDIDIKAN KARAKTER TERHADAP MOTIVASI BELAJAR SISWA KELAS III SD NEGERI 0503 PARSOMBAAN - Daulay, Mukmin Saipul; Era Mutiah; Harahap, Nurhalimah; Daulay, Indah Febriana (Yayasan Perguruan Kampus, 2025)
The purpose of this study was to determine whether there was an influence of character education on the learning motivation of grade III students of SD Negeri 0503 Parsombaan. The method used in this study was quantitative research, this study was conducted at SD Negeri 0503 Parsombaan, the population and sample in this study were grade III students, because the population was relatively small, all populations were used as samples, namely 32 students. The research instrument was made based on the indicators of each variable. With data collection techniques using questionnaires, and documentation. Data analysis techniques using descriptive statistics, prerequisite tests and t-tests. The results of the study obtained were that character education has a relationship with the learning motivation of grade III students of SD Negeri 0503 Parsombaan on the results of the normality test showed that all data obtained had normal data with the consideration of lhitung <ltabel with a value on the character education variable of 0.154 <0.156. Then on the learning motivation variable with a value of 0.136 <0.156. Then in the homogeneity test shows fcount < ftable with a value of 1.033 < 4.171. The results of the t-test obtained show that tcount > ttable (3.927 > 1.697) with a significant value of 0.000 < 0.05. And the results of the R Square test show a value of 0.456 or 45.6%, meaning that character education can contribute 45.6% to the learning motivation of class III students of SD Negeri 0503 Parsombaan.